“I get u”. People correctly interpret the tone of text messages and emails - Monique M.H. Pollmann; Carla A. Roos (Computers in Human Behavior Reports)
It has often been assumed that receivers interpret the emotional tone of a text-based message differently and often more negatively than intended by the sender. It is unclear, however, whether this is true in everyday online conversations between non-strangers. We therefore tested this by comparing sender and receiver ratings of text messages exchanged in an informal context (Study 1) and emails exchanged in a work or educational context (Study 2). In both studies, we asked participants (NStudy1 = 347; NStudy2 = 361) to rate the valence of a message they received and asked the sender of that message (NStudy1 = 171; NStudy2 = 61) to report the intended valence of the message. We tested six possible moderators: (1) the length of the message, (2) the use of emoji, (3) the gender of the receiver, (4) the age of the receiver, (5) the social closeness between sender and receiver, and (6) the degree of neuroticism of the receiver. In both studies, we find no indication for misunderstanding as receivers' and senders' valence ratings align very well. We also find no evidence for moderation effects. This shows that, in the context of everyday text messages and emails, people are able to correctly interpret the emotional valence of a text-based message. This finding challenges the popular assumption of prevalent online misunderstanding and provides empirical support for the idea that people can and do successfully adapt their communication style to accurately convey the emotional tone in text-based messages.